Absence of subharmonic response in vibrated granular systems under microgravity conditions - Kollmer, Jonathan; Tupy, Martin; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Physical Review Applied, 2015)
By means of experiments in microgravity conditions, we show that granular systems subjected to sinusoidal vibrations respond either by harmonic or gaslike dynamics, depending on the parameters of the vibration, amplitude and frequency, and the container size, while subharmonic response is unstable, except for extreme material properties and particular initial conditions. The absence of subharmonic response in vibrated granular systems implies that granular dampeners cannot reveal higher-order resonances, which makes them even more attractive for technical applications. Extensive molecular dynamics simulations support our findings.

Acoustically propelled winged macroparticles - Enriquez Florat, Adriana; Sack, Achim; D'Angelo, Olfa (Journal of Applied Physics, 2024)
Self-propelled particles harvest and harness energy from their environment, transforming it into a controlled force that propels their motion. We present a mechanism to propel active macroparticles using low frequency noise (10-200 Hz). Thin polymer plates (wings) are acoustically excited at their second natural frequency; the mass of air displaced generates a counter-force, which propels the macroparticles. We show that the magnitude and direction of the propelling force can be tweaked through the wing’s shape, dimensions, and orientation. Finally, we design a macroparticle with bidirectional rotation: its rotation direction can be inverted by changing the frequency at which it is excited.
CRIS-Team Scopus Importer:2024-11-29

A device for studying fluid-induced cracks under mixed-mode loading conditions using x-ray tomography - Santarossa, Angel; Ortellado, Laureano; Sack, Achim; Gómez, Leopoldo R.; Pöschel, Thorsten (Review of Scientific Instruments, 2023)
We introduce an innovative instrument designed to investigate fluid-induced fractures under mixed loading conditions, including uniaxial tension and shear stress, in gels and similar soft materials. Equipped with sensors for measuring force, torque, and fluid pressure, the device is tailored for compatibility with x-ray tomography scanners, enabling non-invasive 3D analysis of crack geometries. To showcase its capabilities, we conducted a study examining crack-front segmentation in a hydrogel subjected to air pressure and a combination of tension and shear stress.
CRIS-Team Scopus Importer:2023-08-11

Automated Tomographic Assessment of Structural Defects of Freeze-Dried Pharmaceuticals - Müller, Patric; Sack, Achim; Dümler, Jens; Heckel, Michael; Wenzel, Tim; Siegert, Teresa; Schuldt-Lieb, Sonja; Gieseler, Henning; Pöschel, Thorsten (Aaps Pharmscitech, 2024)
The topology and surface characteristics of lyophilisates significantly impact the stability and reconstitutability of freeze-dried pharmaceuticals. Consequently, visual quality control of the product is imperative. However, this procedure is not only time-consuming and labor-intensive but also expensive and prone to errors. In this paper, we present an approach for fully automated, non-destructive inspection of freeze-dried pharmaceuticals, leveraging robotics, computed tomography, and machine learning.
CRIS-Team Scopus Importer:2024-07-05
Keywords: freeze-drying; lyopohilisate; non-destructive inspection; X-ray tomography

Collective granular dynamics in a shaken container at low gravity conditions - Kollmer, Jonathan; Sack, Achim; Heckel, Michael; Zimber, Fabian; Müller, Patric; Bannerman, Marcus; Pöschel, Thorsten (7th International Conference on Micromechanics of Granular Media: Powders and Grains 2013, 2013)
We investigate the collective dissipative behavior of a model granular material (steel beads) when subjected to vibration. To this end, we study the attenuation of the amplitude of an oscillating leaf spring whose free end carries a rectangular box partly filled with granulate. To eliminate the perturbing influence of gravity, the experiment was performed under conditions of microgravity during parabolic flights. Different regimes of excitation could be distinguished, namely, a gas-like state of disordered particle motion and a state where the particles slosh back and forth between the container walls in a collective way, referred to as collect-and-collide regime. For the latter regime, we provide an expression for the container size leading to maximal dissipation of energy, that also marks the transition to the gas like regime. Also for systems driven at fixed amplitude and frequency, we find both the gas regime and the collect-and-collide regime resulting in similar dissipative behavior as in the case of the attenuating vibration. © 2013 AIP Publishing LL
Keywords: damping; Granular material

Complex velocity dependence of the coefficient of restitution of a bouncing ball - Müller, Patric; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Physical Review Letters, 2013)
We investigate the coefficient of normal restitution as a function of the impact velocity, ε(v), for inelastic spheres. We observe oscillating behavior of ε(v) which is superimposed to the known decay of the coefficient of restitution as a function of impact velocity. This remarkable effect was so far unnoticed because under normal circumstances it is screened by statistical scatter. We detected its clear signature by recording large amounts of data using an automated experiment. The new effect may be understood as an interplay between translational and vibrational degrees of freedom of the colliders. Both characteristics of the oscillation, the wavelength and the amplitude, agree quantitatively with a theoretical description of the experiment. © 2013 American Physical Society.

Discontinuous spirals of stable periodic oscillations - Sack, Achim; Freire, J. G.; Lindberg, Erik; Pöschel, Thorsten; Gallas, Jason (Scientific Reports, 2013)
We report the experimental discovery of a remarkable organization of the set of self-generated periodic oscillations in the parameter space of a nonlinear electronic circuit. When control parameters are suitably tuned, the wave pattern complexity of the periodic oscillations is found to increase orderly without bound. Such complex patterns emerge forming self-similar discontinuous phases that combine in an artful way to produce large discontinuous spirals of stability. This unanticipated discrete accumulation of stability phases was detected experimentally and numerically in a Duffing-like proxy specially designed to bypass noisy spectra conspicuously present in driven oscillators. Discontinuous spirals organize the dynamics over extended parameter intervals around a focal point. They are useful to optimize locking into desired oscillatory modes and to control complex systems. The organization of oscillations into discontinuous spirals is expected to be generic for a class of nonlinear oscillators.

Dissipation of Energy by Dry Granular Matter in a Rotating Cylinder - Sack, Achim; Pöschel, Thorsten (Scientific Reports, 2016)
We study experimentally the dissipation of energy in a rotating cylinder which is partially filled by granular material. We consider the range of angular velocity corresponding to continous and stationary flow of the granulate. In this regime, the stationary state depends on the angular velocity and on the filling mass. For a wide interval of filling levels we find a universal behavior of the driving torque required to sustain the stationary state as a function of the angular velocity. The result may be of relevance to industrial applications, e.g. to understand the power consumption of ball mills or rotary kilns and also for damping applications where mechanical energy has to be dissipated in a controlled wa

Dripping faucet in extreme spatial and temporal resolution - Sack, Achim; Pöschel, Thorsten (American Journal of Physics, 2017)
Besides its importance for science and engineering, the process of drop formation from a homogeneous jet or at a nozzle is of great aesthetic appeal. In this paper, we introduce a low-cost setup for classroom use to produce quasi-high-speed recordings with high temporal and spatial resolution of the formation of drops at a nozzle. The visualization of the process can be used for quantitative analysis of the underlying physical phenomena.

Effect of particle size on the suction mechanism in granular grippers - Santarossa, Angel; D'Angelo, Olfa; Sack, Achim; Pöschel, Thorsten (Granular Matter, 2023)
Abstract: Granular grippers are highly adaptable end-effectors that exploit the reversible jamming transition of granular materials to hold and manipulate objects. Their holding force comes from the combination of three mechanisms: frictional forces, geometrical constraints, and suction effects. In this work, we experimentally study the effect of particle size on the suction mechanism. Through X-ray computed tomography, we show that small particles (average diameter d≈120μm) achieve higher conformation around the object than larger particles (d≈4mm), thus allowing the formation of air-tight seals. When the gripper is pulled off, mimicking lifting of an object, vacuum pressure is generated in the sealed cavity at the interface gripper–object. If the particles used as filling material are too large, the gripper does not conform closely around the object, leaving gaps between the gripper’s membrane and the object. These gaps prevent the formation of sealed vacuum cavities between the object and the gripper and in turn hinder the suction mechanism from operating. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-02-03
Keywords: Computed tomography; Granular gripper; Jamming transition; Soft robotics; Suction

Energy dissipation in driven granular matter in the absence of gravity - Sack, Achim; Heckel, Michael; Kollmer, Jonathan; Zimber, Fabian; Pöschel, Thorsten (Physical Review Letters, 2013)
We experimentally investigate the energy dissipation rate in sinusoidally driven boxes which are partly filled by granular material under conditions of weightlessness. We identify two different modes of granular dynamics, depending on the amplitude of driving, A. For intense forcing, A>A, the material is found in the collect-and-collide regime where the center of mass of the granulate moves synchronously with the driven container, while for weak forcing, A

Erratum to: Stability of freeze-dried products subjected to microcomputed tomography radiation doses - Wenzel, Tim; Sack, Achim; Müller, Patric; Pöschel, Thorsten; Schuldt-Lieb, Sonja; Gieseler, Henning (Journal of Pharmacy and Pharmacology, 2022)
CRIS-Team Scopus Importer:2022-03-11

Fluidization of a horizontally driven granular monolayer - Heckel, Michael; Sack, Achim; Kollmer, Jonathan; Pöschel, Thorsten (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2015)
We consider the transition of a horizontally vibrated monodisperse granular monolayer between its condensed state and its three-dimensional gaseous state as a function of the vibration parameters, amplitude, and frequency as well as particle number density. The transition is characterized by an abrupt change of the dynamical state which leaves its fingerprints in several measurable quantities including dissipation rate, sound emission, and a gap size which characterizes the sloshing motion of the material. The transition and its pronounced hysteresis is explained through the energy due to the collective motion of the particles relative to the container.

Granular dampers for the reduction of vibrations of an oscillatory saw - Heckel, Michael; Sack, Achim; Kollmer, Jonathan; Pöschel, Thorsten (Physica A-Statistical Mechanics and Its Applications, 2012)
Instruments for surgical and dental application based on oscillatory mechanics submit unwanted vibrations to the operator's hand. Frequently the weight of the instrument's body is increased to dampen its vibration. Based on recent research regarding the optimization of granular damping we developed a prototype granular damper that attenuates the vibrations of an oscillatory saw twice as efficiently as a comparable solid mass. © 2012 Elsevier B.V. All rights reserved.
Keywords: Dissipation mechanism; Granular damper; Granular system; Vibrations

Granular dampers in microgravity: sharp transition between modes of operation - Sack, Achim; Windows-Yule, Kit; Heckel, Michael; Werner, Dominik; Pöschel, Thorsten (Granular Matter, 2020)
When a container filled with granular material is subjected to sinusoidal vibration in microgravity, dependent on the amplitude of the oscillation, the granulate may exhibit one of two distinct dynamical modes: at low amplitude, a gas-like state is observed, where the particles are relatively homogeneously distributed within the container, almost independent of the phase of the oscillation. In contrast, for large amplitude, collective motion of the particles is favoured, termed collect-and-collide regime. Both regimes are characterized by very different dissipation characteristics. A recent model predicts that the regimes are separated by a sharp transition due to a critical amplitude of the vibration. Here we confirm this prediction of a sharp transition and also the numerical value of the critical amplitude by means of experiments performed under conditions of weightlessness.
CRIS-Team WoS Importer:2020-05-22

Granularer Greifer - Pöschel, Thorsten; D'Angelo, Olfa; Pucheanu, Walter; Sack, Achim; Santarossa, Angel (2022)
Die Erfindung betrifft einen granu- laren Greifer (1), insbesondere für einen Roboterarm, aufweisend einen Träger (2), eine an dem Träger (2) befestigte Membran (4), die ballonartig einen Innenraum (6) umschließt, ein in den Innenraum (6) eingefülltes Granulat (10), und einen ersten Fluidanschluss (12), der in den Innenraum (6) führt und im bestimmungsgemäßen Betrieb zum Fördern von Fluid aus dem oder in den Innenraum (6) dient. Außerdem weist der Greifer (1) einen glockenartigen Einsatz (14) auf, der in dem Innenraum (6) angeordnet und in einem im bestimmungsgemäßen Betrieb des granularen Greifers (1) einem zu greifenden Objekt zugewandten Bereich mit einem ringartig geschlossenen Rand (20) innen- seitig auf die Membran (4) aufgesetzt ist, und einen zweiten Fluidanschluss (16), der in den Innenraum (6) führt, mit dem Einsatz (14) fluidführungstechnisch verbunden ist und im bestimmungsgemäßen Betrieb zum Fördern von Fluid aus einem oder in einen Zwischenraum (22) zwischen dem Einsatz (14) und der Membran (4) dient.
Keywords: Robotik; Greifer; Jamming in granularen Stoffen

Granular Leidenfrost effect in microgravity - Torres Menendez, Harol; Sack, Achim; Pöschel, Thorsten (Granular Matter, 2020)
When a container filled with granular material is subjected to vertical vibration in the presence of gravity, under certain conditions a non-monotonous density profile can be observed. This effect which is characteristic for dissipative granular gases, was termed “floating cluster regime” or “granular Leidenfrost effect”. Here, we study the behavior of vibro-agitated granular matter in the absence of gravity and identify a corresponding stationary state of the granulate, that is, we provide experimental evidence of the granular Leidenfrost effect under conditions of weightlessness.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Floating cluster; Granular matter; Leidenfrost effect; Microgravity; Parabolic flight; Weightlessness; X-ray radiography

Inexpensive Mie scattering experiment for the classroom manufactured by 3D printing - Scholz, Christian; Sack, Achim; Heckel, Michael; Pöschel, Thorsten (European Journal of Physics, 2016)
Scattering experiments are fundamental for structure analysis of matter on molecular, atomic and sub-atomic length scales. In contrast, it is not standard to demonstrate optical scattering experiments on the undergraduate level beyond simple diffraction gratings. We present an inexpensive Mie scattering setup manufactured with 3D printing and open hardware. The experiment can be used to determine the particle size in dilute monodisperse colloidal suspensions with surprisingly high accuracy and is, thus, suitable to demonstrate relations between scattering measurements and microscopic properties of particles within undergraduate lab course projects.
Keywords: Mie scattering; physics education experiments; 3D printing; open hardware

Microgravity spreading of water spheres on Hydrophobic capillary plates - Steub, Laura; Kollmer, Jonathan; Paxson, Derek; Sack, Achim; Pöschel, Thorsten; Bartlett, John; Berman, Douglas; Richardson, Yaateh; Louge, Michel Y. (EPJ Web of Conferences, 2017)
We create nearly perfect centimetric spheres of water by splitting a cavity consisting of two metal hemispheres coated with a hydrophobic paint and under-filled with liquid, while releasing the apparatus in free-fall. A high-speed camera captures how water spread on hydrophobic aluminum and polycarbonate plates perforated with cylindrical capillaries. We compare observations at the ZARM drop tower in Bremen with Lattice-Boltzmann numerical simulations of Frank, Perré and Li for the inertial phase of imbibition.

Misconceptions about gyroscopic stabilization - Müller, Patric; Sack, Achim; Pöschel, Thorsten (American Journal of Physics, 2020)
A spinning gyroscope resists small torques in directions perpendicular to its axis, that is, the angular orientation of a body rigidly attached to a gyroscope is stable against rotation around certain axes. Since the angular orientation of a body is described by three angles (e.g., Euler angles), one might conclude that it is possible to stabilize the orientation of an object against rotation using a combination of three gyroscopes spinning around non-collinear axes. We perform experiments under conditions of weightlessness to demonstrate that systems of coupled gyroscopes cannot arrest the angular orientation of free-floating objects, in contradiction to a widespread myth about gyroscopic stabilization, based on the above arguments. (C) 2020 American Association of Physics Teachers.
CRIS-Team WoS Importer:2020-06-26

Movers and shakers: Granular damping in microgravity - Bannerman, Marcus; Kollmer, Jonathan; Sack, Achim; Heckel, Michael; Müller, Patric; Pöschel, Thorsten (Physical Review E, 2011)
The response of an oscillating granular damper to an initial perturbation is studied using experiments performed in microgravity and granular dynamics simulations. High-speed video and image processing techniques are used to extract experimental data. An inelastic hard sphere model is developed to perform simulations and the results are in excellent agreement with the experiments. In line with previous work, a linear decay of the amplitude is observed. Although this behavior is typical for a friction-damped oscillator, through simulation it is shown that this effect is still present even when friction forces are absent. A simple expression is developed which predicts the optimal damping conditions for a given amplitude and is independent of the oscillation frequency and particle inelasticities. © 2011 American Physical Society.

Pattern formation in a horizontally shaken granular submonolayer - Krengel, Dominik; Strobl, Severin; Sack, Achim; Heckel, Michael; Pöschel, Thorsten (Granular Matter, 2013)
We study the mechanism leading to the formation of stripe-like patterns in a rectangular container filled with a sub-monolayer of frictional spherical particles when it is subjected to horizontal oscillations. By means of Molecular Dynamics simulations we could reproduce the experimental results. Systematic simulations allow to identify friction to be responsible for the pattern formation, that is, the tangential interaction between contacting particles and between the particles and the floor of the container. When particles are in contact with the floor and other adjacent particles simultaneously, there emerges a frustrated situation in which the particles are prevented from rolling on the floor. This effect leads to local jamming and eventually to stripe-like pattern formation. In the long time evolution, the stripes are unstable. Stripes may merge as well as disintegrate. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Frustration effects; Horizontal shaking; Pattern formation

Probing the validity of an effective-one-particle description of granular dampers in microgravity - Sack, Achim; Heckel, Michael; Kollmer, Jonathan; Pöschel, Thorsten (Granular Matter, 2014)
We consider the attenuation of the oscillation of a flat spring due to the action of a granular damper. The efficiency of the damper is quantified by evaluating the position of the oscillator as a function of time using a Hall effect based position sensor. Performing experiments for a large abundance of parameters under conditions of microgravity, we confirm a recent theory for granular damping (Kollmer et al. in New J Phys 15:093023, 2013) and show that the theory remains approximately valid even beyond the limits of its derivation.
Keywords: Dissipation; Granular systems; Vibration damping

Relaxation of a spring with an attached granular damper - Kollmer, Jonathan; Sack, Achim; Heckel, Michael; Pöschel, Thorsten (New Journal of Physics, 2013)
The oscillation of a spring may be attenuated by means of a granular damper. In difference to viscous dampers, the amplitude decays nearly linearly in time up to a finite value, from there on it decays much slower. We quantitatively explain the linear decay, which was a long-standing question. © IOP Publishing and Deutsche Physikalische Gesellschaft.

Soft particles reinforce robotic grippers: robotic grippers based on granular jamming of soft particles - Götz, Holger; Santarossa, Angel; Sack, Achim; Pöschel, Thorsten; Müller, Patric (Granular Matter, 2022)
Granular jamming has been identified as a fundamental mechanism for the operation of robotic grippers. In this work, we show, that soft particles like expanded polystyrene beads lead to significantly larger gripping forces in comparison to rigid particles. In contradiction to naive expectation, the combination of jamming and elasticity gives rise to very different properties of the jammed phase, compared to hard-particle systems. This may be of interest also beyond the application in robotic grippers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Granular gripper; Granular jamming; Soft robotics

Stability of freeze-dried products subjected to microcomputed tomography radiation doses - Wenzel, Tim; Sack, Achim; Müller, Patrick; Pöschel, Thorsten; Schuldt-Lieb, Sonja; Gieseler, Henning (Journal of Pharmacy and Pharmacology, 2021)
OBJECTIVES: Microcomputed tomography (µCT) is a powerful analytical tool for non-invasive structural analysis. The stability of drug substances and formulations subjected to X-ray radiation may be a concern in the industry. This study examines the effect of X-ray radiation on the stability of freeze-dried pharmaceuticals. The investigation is a proof of concept study for the safety of µCT X-ray radiation doses during the non-destructive investigation of freeze-dried products. METHODS: Different formulations of clotrimazole, insulin and l-lactate dehydrogenase were freeze-dried and the products exposed to a defined dose of radiation by µCT. Conservative freeze-drying conditions were used. Irradiated and normal samples were analysed for their stability directly after freeze-drying and after stability testing. KEY FINDINGS: The stability of model compounds was well maintained during freeze-drying. Some degradation of all compounds occurred during accelerated stability testing. The results showed no differences between the irradiated and normal state directly after freeze-drying and accelerated stability testing. CONCLUSIONS: No evidence of a detrimental effect of 100 Gy X-ray exposure on a model small molecule, peptide and protein compound was found while useful structural information could be obtained. Consequently, the technology may be useful as a non-destructive tool for product inspections if the formulation proves stable.
CRIS-Team Scopus Importer:2021-04-16
Keywords: freeze-drying; inspection; micro computed tomography; morphology; stability

TSS-ConvNet for electrical impedance tomography image reconstruction - Ameen, Ayman A.; Sack, Achim; Pöschel, Thorsten (Physiological Measurement, 2024)
Objective. The objective of this study was to propose a novel data-driven method for solving ill-posed inverse problems, particularly in certain conditions such as time-difference electrical impedance tomography for detecting the location and size of bubbles inside a pipe. Approach. We introduced a new layer architecture composed of three paths: spatial, spectral, and truncated spectral paths. The spatial path processes information locally, whereas the spectral and truncated spectral paths provide the network with a global receptive field. This unique architecture helps eliminate the ill-posedness and nonlinearity inherent in the inverse problem. The three paths were designed to be interconnected, allowing for an exchange of information on different receptive fields with varied learning abilities. Our network has a bottleneck architecture that enables it to recover signal information from noisy redundant measurements. We named our proposed model truncated spatial-spectral convolutional neural network (TSS-ConvNet). Main results. Our model demonstrated superior accuracy with relatively high resolution on both simulation and experimental data. This indicates that our approach offers significant potential for addressing ill-posed inverse problems in complex conditions effectively and accurately. Significance. The TSS-ConvNet overcomes the receptive field limitation found in most existing models that only utilize local information in Euclidean space. We trained the network on a large dataset covering various configurations with random parameters to ensure generalization over the training samples.
CRIS-Team Scopus Importer:2024-05-03
Keywords: deep neural network; electrical impedance tomography; ill posed inverse problems; truncated spatial-spectral convolutional neural network

Weight of an Hourglass – Theory and Experiment in Quantitative Comparison - Sack, Achim; Pöschel, Thorsten (American Journal of Physics, 2017)
A flowing hourglass changes its weight in the course of time because of the accelerated motion of its center of mass. While this insight is not new, it is frequently said that the effect is tiny and hardly measurable. Here we present a simple experiment which allows to monitor the weight as a function of time revealing different stages, in quantitative agreement with theory.

X-ray tomography in micro-gravity - Torres Menendez, Harol; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Review of Scientific Instruments, 2019)
We present an X-ray device for use under conditions of weightlessness to produce high-speed radiograms and tomograms. The device is equipped with two detectors of different resolutions, a high temporal resolution-small area detector (4 Mpix within 13 × 13 mm2) and a low temporal resolution-large area detector (3 Mpix within 145 × 115 mm2). Using the high temporal resolution detector, the device achieves a recording rate of up to 25 655 radiograms per second, while using a low temporal resolution detector, up to 86 radiograms can be recorded per second. For the first time, we could record complete X-ray tomograms in microgravity aboard a parabolic flight in 16 s using a laboratory microfocus X-ray source. We demonstrate the operation of the device by analyzing the three-dimensional packing of particles (tomograms) and structure formation in a granular gas under periodic excitation (radiograms).
CRIS-Team Scopus Importer:2019-10-22